Svetloba zvezd kot energija za teritorialni razvoj Ekstremadure - Logar, Erik (Geografski obzornik, 2025)
The Spanish region of Extremadura, through the Extremadura Buenas Noches (EBN) initiative, seeks to preserve the dark night sky as a natural resource and promote astrotourism. The initiative has developed observation sites, marked night trails, and facilitated educational and professional activities. Its goals include enhancing awareness of the night sky‘s value, addressing light pollution, fostering economic development, encouraging innovation, and creating green jobs. This initiative serves as an example of good practice that could inspire similar efforts in Slovenia.
Keywords: astronomija; astrotourism; astroturizem; Ekstremadura; Extremadura; light pollution; local communities; lokalne skupnosti; night sky; nočno nebo; Spain; svetlobno onesnaženje; Španija; teritorialni razvoj; territorial development